Carbon stock and its responses to climate change in Central Asia. (27th January 2015) - Li, Chaofan; Zhang, Chi; Luo, Geping; Chen, Xi; Maisupova, Bagila; Madaminov, Abdullo A.; Han, Qifei; Djenbaev, Bekmamat M.
Abstract: Central Asia has a land area of 5.6 × 10 6  km 2 and contains 80–90% of the world's temperate deserts. Yet it is one of the least characterized areas in the estimation of the global carbon (C) stock/balance. This study assessed the sizes and spatiotemporal patterns of C pools in Central Asia using both inventory (based on 353 biomass and 284 soil samples) and process‐based modeling approaches. The results showed that the C stock in Central Asia was 31.34–34.16 Pg in the top 1‐m soil with another 10.42–11.43 Pg stored in deep soil (1–3 m) of the temperate deserts. They amounted to 18–24% of the global C stock in deserts and dry shrublands. The C stock was comparable to that of the neighboring regions in Eurasia or major drylands around the world (e.g. Australia). However, 90% of Central Asia C pool was stored in soil, and the fraction was much higher than in other regions. Compared to hot deserts of the world, the temperate deserts in Central Asia had relatively high soil organic carbon density. The C stock in Central Asia is under threat from dramatic climate change. During a decadal drought between 1998 and 2008, which was possibly related to protracted La Niña episodes, the dryland lost approximately 0.46 Pg C from 1979 to 2011. The largest C losses were found in northern Kazakhstan, where annual precipitation declined at a rate of 90 mm decade −1 . The regional C dynamics were mainly determined by changes in the vegetation C pool, and the SOC pool was stable due to the balance between reduced plant‐derived C influx and inhibited respiration.